The Effect of Volume Target on Quality of Radiotherapy using 3DCRT and IMRT: Dosimetry and Radiobiological Evaluation - Lutfin, Nursakinah Annisa; Widita, Rena (Universitas Sebelas Maret, 2023)
The main goal of radiotherapy is to deliver the maximum possible dose to the target volume and the minimum possible to the surrounding healthy tissue. In this study, planning was carried out on the TPS Eclipse Varian Medical System using 3DCRT and IMRT techniques for 14 cancer patients. 6 cases of lung cancer with PTV were in the range of 175.1 cc - 875.5 cc, and eight brain cancer patients with a PTV range of 148.5 cc - 841.2 cc. This study aims to determine the effect of target volume on the quality of radiation therapy planning using the 3DCRT and IMRT techniques. The evaluation was carried out using dosimetry and radiobiology analysis. Dosimetry assessment analyzes the average dose, D98, D50, D2, CI, and HI on PTV and the average dose on OAR. Radiobiological evaluation by calculating the value of TCP, NTCP, and UTCP. The results showed that based on dosimetry and radiobiology evaluation, the IMRT technique provides better planning quality for radiation therapy by increasing the probability of cancer cells dying at PTV and reducing the risk of OAR compared to planning using the 3DCRT technique. The effect of PTV on planning quality using statistical regression tests showed that PTV did not significantly impact the quality of radiation therapy planning results either using the 3DCRT technique or the IMRT technique.